Computational Investigation of Voltage-Gated Sodium Channel β3 Subunit Dynamics - Glass, William G.; Duncan, Anna L.; Biggin, Philip C. (Frontiers in Molecular Biosciences, 2020)
Voltage-gated sodium (Nav) channels form the basis for the initiation of the action potential in excitable cells by allowing sodium ions to pass through the cell membrane. The Nav channel α subunit is known to function both with and without associated β subunits. There is increasing evidence that these β subunits have multiple roles that include not only influencing the voltage-dependent gating but also the ability to alter the spatial distribution of the pore-forming α subunit. Recent structural data has shown possible ways in which β1 subunits may interact with the α subunit. However, the position of the β1 subunit would not be compatible with a previous trimer structure of the β3 subunit. Furthermore, little is currently known about the dynamic behaviour of the β subunits both as individual monomers and as higher order oligomers. Here, we use multiscale molecular dynamics simulations to assess the dynamics of the β3, and the closely related, β1 subunit. These findings reveal the spatio-temporal dynamics of β-subunits and should provide a useful framework for interpreting future low-resolution experiments such as atomic force microscopy